Biomass Production of Selected Energy Plants: Economic Analysis and Logistic Strategies; Analiza ekonomiczna i strategie logistyczne produkcji biomasy wybranych rosĺin energetycznych - Agata Pszczoĺkowska; Zdzisława Romanowska-Duda; Wiktor Pszczoĺkowski; Mieczysław Grzesik; Zofia Wysokinśka (Comparative Economic Research. Central and Eastern Europe, 2012)
The objective of this article is the conducting of an analysis of the production of selected energy plants that are already a basic source of agrobiomass in Poland. The analysis looks at environmental aspects and production conditions for biomass designated for energy for the Virginia mallow (Sida hermaphrodita), common osier (Salix viminalis), silver-grass (Miscanthus x giganteus), and switchgrass (Panicum virgatum). What is presented is an economic analysis of the production of selected energy plants, taking into account the costs of establishing plantations and their cost effectiveness. Moreover, logistic strategies for the delivery of biomass intended to secure continuous production of renewable energy as a part of sustainable development is signaled. – – Celem nieniejszego artykułu było przeprowadzenie analizy produkcji wybranych rosĺin energetycznych, ktoŕe w Polsce sa juzṗodstawowym zŕod́łem agrobiomasy. W tresći analiza zawierała aspekty sŕodowiskowe i uwarunkowania produkcji biomasy na cele energetyczne dla sĺazowca pensylwanśkiego (Sida hermaphrodita), wierzby wiciowej z rodzaju Salix,i miskanta olbrzymiego (Miscanthus x giganteus) i prosa roźgowatego (Panicum virgatum). Przedstawiono analize ekonomiczna produkcji wybranych rosĺin energetycznych z uwzglednieniem kosztoẃ plantacji i ich opłacalnosći oraz zasygnalizowano strategie logistyczne dla dostaw biomasy w celu zabezpieczenia stałej produkcji energii odnawialnej w zroẃnowazȯnym rozwoju.
Keywords: 330